Myofascial Structural Integration Therapy on Gross Motor Function and Gait of Young Children with Spastic Cerebral Palsy: A Randomized Controlled Trial - Loi, Elizabeth C.; Buysse, Christina A.; Price, Karen S.; Jaramillo, Theresa M.; Pico, Elaine L.; Hansen, Alexis B.; Feldman, Heidi M. (Frontiers in Pediatrics, 2015)
Though the cause of motor abnormalities in cerebral palsy is injury to the brain, structural changes in muscle and fascia may add to stiffness and reduced function. This study examined whether Myofascial Structural Integration therapy (MSI), a complementary treatment that manipulates muscle and fascia, would improve gross motor function and gait in children < 4 years with cerebral palsy. Participants (N=29) were enrolled in a randomized controlled trial (RCT: NCT01815814, https://goo.gl/TGxvwd) or Open Label Extension. The main outcome was the Gross Motor Function Measure-66 assessed at 3-month intervals. Gait (n=8) was assessed using the GAITRite® electronic walkway. Parents completed a survey at study conclusion. Comparing Treatment (n=15) and Waitlist-Control Groups (n=9), we found a significant main effect of time but no effect of group or timeXgroup interaction. The pooled sample (n=27) showed a main effect of time, but no significantly greater change after treatment than between other assessments. Foot length on the affected side increased significantly after treatment, likely indicating improvement in the children’s ability to approach a heel strike. Parent surveys indicated satisfaction and improvements in the children's quality of movement. MSI did not increase the rate of motor skill development, but was associated with improvement in gait quality.